Peran Keluarga Terhadap Keputusan Remaja Menikah Dini - Astika, Nova; Apriani, Lia Arian; Yulastini, Fitria; Fajriani, Evalina; Wiguna, Reza Indra (Jurnal Kebidanan Malakbi, 2025)
Indonesia faces a significant challenge with child marriage, ranking second highest in ASEAN after Cambodia. This alarming trend has seen a concerning increase, highlighting the urgent need for effective interventions. In 2020 alone, NTB Province recorded 805 cases of underage marriage, emphasizing the critical nature of this issue within the region. This study aims to investigate the crucial role of family and the level of adolescent knowledge regarding early marriage in contributing to this concerning phenomenon. This study employed an analytical observational method with a cross-sectional design, conducted at SMPN 02 Batukliang in Central Lombok Regency, involving 98 adolescent students as participants. The results of the study revealed that 39.8% of respondents belonged to families with either "good" or "sufficient" levels of family role, while 20.4% belonged to families with a "poor" level of family role. Regarding adolescent knowledge about early marriage, 36.7% of respondents (36 individuals) exhibited a "good" level of knowledge, and 43.9% (43 individuals) demonstrated a "sufficient" level of knowledge. Data analysis utilizing the chi-square test yielded a statistically significant result (p-value = 0.001), indicating a strong association between family role and adolescent knowledge about early marriage among students at SMPN Satu Atap 02 Batukliang in Batukliang District, Central Lombok Regency. This research concludes that effective parental guidance significantly influences adolescents' knowledge regarding future marriage plans, indirectly contributing to the prevention of underage marriage.